Behavioral Insights Into Investment Decision-Making: Evidence From the Nepal Stock Exchange - Pathak, Durga Datt; Puri, Sirish; Thapa, Bharat Singh (The Batuk, 2024)
This paper provides a reliable foundation for investigating how people's behaviors influence investment decisions. The study surveyed 286 individual investors who participated in the Nepal Stock Exchange, employing a purposive sampling procedure and self-administered structured Likert scale questionnaire. The results indicate that behavioral factors, including stock affordability, information availability, third-party opinions, and herding effect, significantly influence individual investors’ rationality in making investment decisions. The study concludes that in a developing and expanding environment, factors such as disposable income, market trends, and external opinions notably shape investment decisions when individuals choose to invest in the stock market. The alignment of our findings with existing literature reinforces the robustness of our results. The implications of these findings extend to investors, financial advisors, and policymakers alike. Recognizing the influence of behavioral factors can aid in developing strategies to promote informed decision-making and mitigate the adverse effects of herding behavior.